Analisis Kinerja Waktu dan Penerapan Building Information Modeling pada Proyek Pembangunan Jasmine Park Apartment Bogor: Time Schedule Analysis and Building Information Modeling Application on Jasmine Park Apartment Bogor - Ahmad Ulil Albab; Erizal (Jurnal Teknik Sipil dan Lingkungan, 2021)
Increasing of certainly development requires jobs with high productivity, effectiveness and efficiency. The application of BIM up to four-dimensional modeling (4D) using Tekla Structure software is a solution because it can analyze time performance, determine the causative factors in the event of delays and actions to overcome them. 3D modeling included modeling of foundations, columns, beams, slabs, stairs, and roofs. 4D modeling is conducted by adding work schedule to the 3D modeling that had been made. Time performance analysis was performed using the S-curve method for all buildings in Tower Green Jasmine Park Apartment Bogor construction project. Time performance analysis using the S curve found that this project experienced delays with the highest negative deviation value happened in June 2020 by -13.67%. The main delays in the project occured in procurement of MEP logistics and weather conditions. Work acceleration is carried out by increasing working hours and increasing the number of workers.